Experimental investigations to improve the electrical efficiency of photovoltaic modules using different convection mode. (December 2021) - Santhosh Kumar, P.C.; Naveenkumar, R.; Sharifpur, Mohsen; Issakhov, Alibek; Ravichandran, M.; Mohanavel, V.; Aslfattahi, Navid; Afzal, Asif
Graphical abstract: Highlights: Experimental analysis of four different convection modes in solar PV panels. Maximum current, voltage generation, and maximum heat removal for 3 days is calculated. Without and with duct under free convection solar panel base panel temperature. With duct under forced convection and duct with L shaped barrier is analyzed. Maximum electrical efficiency enhancement of 21.68% with duct and L shaped barrier. Abstract: Solar energy is the most frequently used renewable energy source which receives the light energy from the sun, and it transform in to electric energy with the help of photovoltaic cell as a module. The flow of electrons or electrical energy is produced by making the sunlight photons to fall on the collector. Which produce the electrical energy, but the power generation is not completely produced because due to various losses. The most commonly occurred power loss is due to heat formed under the solar panel which affects the solar panel performance. Induced electrical energy is inversely proportional to the base panel temperature. Our main scope of the work is to remove the heat, which are accumulated under the solar panel by using different convection mode. In this paper, an experimental analysis is conducted in four different convection mode for heat removal for three days from sunrise 8.00 a.m. to 5.00 p.m. for calculating the maximum current, voltage generation and maximum heat removal. Four experiments namely, without rectangular duct under free convection, with rectangular duct under free convection, with rectangular duct under forced convection and duct with L shaped barrier and forced convection are conducted for three days. The maximum voltage induced in solar panel without duct, with duct under free convection, duct under forced convection and duct under forced convection & L shaped barrier was obtained at 11:00 a.m. as 18.54 V, 19.05 V, 21.04 V and 22.56 V. Results indicate that the maximum voltage induced is significantly increased in all the modifications such as duct under free convection, duct under forced convection and duct under forced convection & L shaped barrier by 2.75%, 13.48% and 21.68% as compared to conventional solar panel without duct condition. The inclusion of duct under free convection, duct under forced convection and duct under forced convection & L shaped barrier in solar panel base limits the maximum temperature as 44℃, 41℃ and 38℃, however the maximum temperature in the solar panel base is 49℃ for solar panel without duct condition. Reduction in solar panel base maximum temperature for duct under free convection, duct under forced convection and duct under forced convection & L shaped barrier are 10.20%, 16.33% and 22.45% as compared to conventional solar panel without duct condition. The results also indicate that the induced voltage and solar panel base panel temperature for four experiments was compared and found the maximum electrical efficiency enhancement of 21.68% with duct and L shaped barrier under forced convection than conventional method and the corresponding base panel temperature reduction is 19.15% is obtained than conventional type. The proposed system significantly increased the photovoltaic panel performance and output voltage due to enhanced evaporation rate and reduction in photovoltaic panel temperature.